Performance of A Triboelectric Nanogenerator Utilising Coconut Husk Layer - Saparin M.A.; Salleh H.; Hen C.K.; Amnuruddin S.N.A. (UiTM Press, 2025)
Triboelectric nanogenerators, known as TENGs, offer great potential as versatile energy harvesting devices. In recent years, there has been a rise in TENG designs that prioritize compatibility with sustainable biomaterials, leading to new possibilities in green technology. The novelty of this work lies in its pioneering exploration of utilizing sustainable biomaterials, particularly coconut husk, within the field of Tribo-electric nanogenerators (TENGs). This study focuses on evaluating and characterizing coconut husk as TENG material considering factors such as rotational speed, vane count, and coarseness, all of which influence the output potential of the B-TENG. The B-TENG model employed in this research operates on a rotational sliding mode, featuring a biobased material layer of coconut husk, a layer of PTFE, and copper as electrodes. The B-TENG has a diameter of 100 mm with varying vane configurations (3-vane, 4-vane, and 5-vane). The sliding mode demonstrated impressive versatility, yielding output voltages spanning from 0.73 V to 4.0 V across rotational speeds of 200 RPM to 1400 RPM. Remarkably, the 5-vane fine-grained coconut husks achieved a maximum power of 121.10 mW at 10 Ohm and a power density of 3.84 mW/cm2. This research carries global significance, contributing to the advancement of energy harvesting technology. Its applications range from harnessing the motion of human bodies to rotating machineries in any industry. ? 2024 College of Engineering, Universiti Teknologi MARA (UiTM), Malaysia. https://doi.org/10.24191/jmeche.v21i3.27350